Phenotypic Modulation of Cultured Primary Human Aortic Vascular Smooth Muscle Cells by Uremic Serum - Cazaña-Pérez, Violeta; Cidad, Pilar; Donate-Correa, Javier; Martín-Núñez, Ernesto; López-López, José R.; Pérez-García, M. Teresa; Giraldez, Teresa; Navarro-González, Juan F.; Alvarez de la Rosa, Diego (Frontiers in Physiology, 2018)
Patients with chronic kidney disease (CKD) have a markedly increased incidence of cardiovascular disease (CVD). The high concentration of circulating uremic toxins and alterations in mineral metabolism and hormone levels produce vascular wall remodelling and significant vascular damage. Medial calcification is an early vascular event in CKD patients and is associated to apoptosis or necrosis and trans-differentiation of vascular smooth muscle cells (VSMC) to an osteogenic phenotype. VSMC obtained from bovine or rat aorta and cultured in the presence of increased inorganic phosphate (Pi) have been extensively used to study these processes. In this study we used human aortic VSMC primary cultures to compare the effects of increased Pi to treatment with serum obtained from uremic patients. Uremic serum induced calcification, trans-differentiation and phenotypic remodelling even with normal Pi levels. In spite of similar calcification kinetics, there were fundamental differences in osteochondrogenic marker expression and alkaline phosphatase induction between Pi and uremic serum-treated cells. Moreover, high Pi induced a dramatic decrease in cell viability, while uremic serum preserved it. In summary, our data suggests that primary cultures of human VSMC treated with serum from uremic patients provides a more informative model for the study of vascular calcification secondary to CKD.